Spatial analysis of groundwater level monitoring network in the Danube-Tisza Interfluve using semivariograms - Kohán, Balázs; Szalai, József (Hungarian Geographical Bulletin, 2014)
Over the last thirty years in the Danube-Tisza Ridge the main factor restraining agricultural activity and in general the size of the nature reserve areas of the Kiskunság National Park has been the lack of water. The fluctuation of the water resources affecting the plain areas in general is indicated by the decrease of the groundwater level. This decrease summarizes the effects of all the influencing phenomena. After the decreasing trend of groundwater-level has been realized, studies aiming to determine the causes and the extent of the phenomenon have been carried out. Unlike previous approaches found in literature, the present study does not analyze the different groundwater levels as time series. Instead, it deals with the spatial relationship of the measurements at certain moments of time using spatial semivariogram analysis on hydrographs of shallow groundwater data, in order to (i) analyse the spatial structure of the groundwater level monitoring well system and (ii) to recalibrate it, based on the results of the study. The results indicated, that the correlation between groundwater level and elevation is periodically changing, but very strong. Furthermore it was shown that the spatial variability of groundwater-level variations can be observed with half as many stations as the existing one, if they were arranged in a more optimal way.